2021
DOI: 10.1111/imj.15241
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world off‐label use of icatibant for acute management of non‐hereditary angioedema

Abstract: We retrospectively examined the indications and efficacy of off‐label use of the bradykinin B2 receptor antagonist icatibant. The clinical heterogeneity, variability of response to icatibant and lack of efficacy of adrenaline described in this audit highlights both the need for biomarkers that can rapidly distinguish between histaminergic and non‐histaminergic angioedema, and for guidelines to improve the utility of icatibant in the non‐hereditary angioedema setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…We noted an underprescription of epinephrine in treating angioedema attacks of unknown origin with a prior epinephrine administration in only one third of first swelling episodes. Our results are far below those from a recent Australian study on off‐label use of icatibant 18 . In that study, epinephrine was provided before icatibant in 15 of the 18 prescriptions, while most cases were also for drug‐induced angioedema.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…We noted an underprescription of epinephrine in treating angioedema attacks of unknown origin with a prior epinephrine administration in only one third of first swelling episodes. Our results are far below those from a recent Australian study on off‐label use of icatibant 18 . In that study, epinephrine was provided before icatibant in 15 of the 18 prescriptions, while most cases were also for drug‐induced angioedema.…”
Section: Discussioncontrasting
confidence: 95%
“…Our results are far below those from a recent Australian study on off-label use of icatibant. 18 In that study, epinephrine was provided before icatibant in 15 of the 18 prescriptions, while most cases were also for drug-induced angioedema. By contrast, Cai et al 17 reported a proportion of about 30% of prior administration of epinephrine in real-life prescriptions of icatibant, which is comparable to our findings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although bradykinin-targeted therapy is useful for hereditary angioedema, it might also be useful for the treatment of drug-induced angioedema. Icatibant is effective for ACE inhibitor-triggered angioedema, which is also involved in the enhancement of bradykinin production, suggesting that treatment based on etiology is essential for the treatment of angioedema [27].…”
Section: Medical-agent-mediated Angioedema As Non-ige Mediated Angioedemamentioning
confidence: 99%